Active listening, shared decision-making and participation in care among older women and primary care nurses: a critical discourse analysis approach from a gender perspective - Pablo Martínez-Angulo; Manuel Rich-Ruiz; M. Rocío Jiménez-Mérida; Salvador López-Quero (BMC, 2024)
Abstract Background Nursing care for older women represent a challenge worldwide due to its characteristics. When communication is impaired between primary care nurses and older women living alone, an imbalance in power relations occurs. The main objective of this study is to analyse the power relations between older women and primary care nurses in situations of active listening, shared decision-making and participation in care. Methods We developed a qualitative study in southern Spain using a discursive and gender approach. We used purposeful sampling to interview older women who lived alone and received home nursing care. Simultaneously, we conducted focus groups with primary care nurses who provided home care to older women. A linguistic analysis of the transcripts was carried out. Results Nine semi-structured face-to-face interviews were conducted with older women who lived alone and two face-to-face focus groups with four primary care nurses in each. The discourse of the participants demonstrated an imbalance in power relations. Influenced by work overload, active listening was considered a privilege in primary care nurses´ discourse. Regarding shared decision-making, older women´s discourses revealed "mirages" of real situations where they thought they were deciding. Participation in care was difficult since older women saw themselves as a nuisance in nurses´ presence, and primary care nurses did not facilitate older women's engagement. Older women weren´t considered when organising home visits and had interiorised a subordinated feeling. Similarly, a strict sense of identity made primary care nurses feel powerful in their relationships with older women. Conclusions The discourse of older women represented them as victims of a hostile panorama whilst they were sometimes satisfied with the deficient care received. The discourse of primary care nurses used more discursive strategies to represent themselves as professionals committed to caring. However, it also revealed deficiencies in care, discriminatory elements, and feelings of being limited by their working conditions. Active listening to older women and engagement in decision-making readjust empower the older women. Attending to the needs and concerns of primary care nurses could recalibrate the power imbalance between them and healthcare organisations.